Formation of Proton Motive Force Under Low-Aeration Alkaline Conditions in Alkaliphilic Bacteria - Matsuno, Toshihide; Goto, Toshitaka; Ogami, Shinichi; Morimoto, Hajime; Yamazaki, Koji; Inoue, Norio; Matsuyama, Hidetoshi; Yoshimune, Kazuaki; Yumoto, Isao (Frontiers in Microbiology, 2018)
In Mitchell’s chemiosmotic theory, a proton (H+) motive force across the membrane (Δp), generated by the respiratory chain, drives F1Fo-ATPase for ATP production in various organisms. The bulk-base chemiosmotic theory cannot account for ATP production in alkaliphilic bacteria. However, alkaliphiles thrive in environments with a H+ concentrations that are one-thousandth (ca. pH 10) the concentration required by neutralophiles. This situation is similar to the production of electricity by hydroelectric turbines under conditions of very limited water. Alkaliphiles manage their metabolism via various strategies involving the cell wall structure, solute transport systems and molecular mechanisms on the outer surface membrane. Our experimental results indicate that efficient ATP production in alkaliphilic Bacillus spp. is attributable to a high membrane electrical potential (ΔΨ) generated for an attractive force for H+ on the outer surface membrane. In addition, the enhanced F1Fo-ATPase driving force per H+ is derived from the high ΔΨ. However, it is difficult to explain the reasons for high ΔΨ formation based on the respiratory rate. The Donnan effect (which is observed when charged particles that are unable to pass through a semipermeable membrane create an uneven electrical charge) likely contributes to the formation of the high ΔΨ because the intracellular negative ion capacities of alkaliphiles are much higher than those of neutralophiles. There are several variations in the adaptation to alkaline environments by bacteria. However, it could be difficult to utilize high ΔΨ in the low aeration condition due to the low activity of respiration. To explain the efficient ATP production occurring in H+-less and air-limited environments in alkaliphilic bacteria, we propose a cytochrome c-associated “H+ capacitor mechanism” as an alkaline adaptation strategy. As an outer surface protein, cytochrome c-550 from Bacillusclarkii possesses an extra Asn-rich segment between the region anchored to the membrane and the main body of the cytochrome c. This structure may contribute to the formation of the proton-binding network to transfer H+ at the outer surface membrane in obligate alkaliphiles. The H+ capacitor mechanism is further enhanced under low-aeration conditions in both alkaliphilic Bacillus spp. and the Gram-negative alkaliphile Pseudomonas alcaliphila.